Perspektif Guru dalam Literasi Sains pada Pembelajaran IPA: Survey Deskriptif - Indra Budiman; Ida Kaniawati; Anna Permanasari; Iwa Lukmana (Postgraduate, University of Mataram, 2021)
Survey of questionnaire-based research was conducted to assess the perspective of junior high school (JHS) science teachers on scientific literacy in science learning. Four perspectives for teachers in JHS on scientific literacy were obtained from the research results of the experiments, namely the reading of scientific texts, scientific knowledge, the use of science in everyday life and the use of science-based learning tools. The majority of participants chose the response choice to train all students to apply science learning results in decision-making on daily life challenges. Thus, JHS Science Teachers in Purwakata Regency have a variety of scientific literacy perspectives, but there is no perspective that is considered outside the context of scientific literacy